A Living Biotic–Abiotic Composite that can Switch Function Between Current Generation and Electrochemical Energy Storage. (6th November 2020) - Su, Yude; McCuskey, Samantha R.; Leifert, Dirk; Moreland, Alex S.; Zhou, Lingyun; Llanes, Luana C.; Vazquez, Ricardo J.; Sepunaru, Lior; Bazan, Guillermo C.
Abstract: Power generation and charge storage devices are commonly uncoupled when it comes to the design of materials relevant for their fabrication. Here, it is demonstrated that the biotic–abiotic composite comprising the self‐doped conjugated polyelectrolyte CPE‐K and electrogenic bacteria Shewanella oneidensis MR‐1 can reversibly switch its function between electrical current generation in chronoamperometry mode (≈150 mA m −2 ) and electrochemical energy storage as a pseudocapacitor with a specific capacitance of up to 80 F g −1 . Interconversion of desirable properties for the different functions is achieved by the simple addition and removal of Mg 2+ in the bulk electrolyte. Potentiostatic, galvanostatic, and electrochemical impedance spectroscopy characterization, accompanied by imaging and cell viability tests, indicate that the modulation of properties is a result of reversible changes in CPE‐K macrostructures and in the number of living bacteria within the composite. The results show the possibility to realize an "on‐demand" switch between current generation and charge storage by one integrated "living" material. Abstract : A biotic–abiotic composite comprising the self‐doped conjugated polyelectrolyte CPE‐K and electrogenic bacteria Shewanella oneidensis MR‐1 can reversibly switch its function between electrical current generation and electrochemical energy storage. Interconversion of desirable properties for the different functions is achieved by the addition or removal of Mg 2+ in the bulk electrolyte.